AGE-specificity in acute pain syndrome measurement in otorhinolaryngology - V I Popadyuk (RUDN Journal of Medicine, 2012)
In this study, 133 patients were divided by age into three groups. First group: from 17 to 29 years old; second group: from 30 to 49 years old; and third group: from 50 to 75 years old. Pain intensity of patients was measured by means of a Visual Analogue Scale (VAS), of a Numeric Rating Scale (NRS) and of a Verbal Lightning Scale (LS). All three scales could be used in measurement of pain of patients of the first group whereas NRS is preferable for the second group and LS - for the third group.